Competition Between For-Profit and Non-Profit Firms: Incentives, Workers' Self-Selection, and Wage Differentials - Francesca Barigozzi; Nadia Burani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
We study optimal non-linear contracts offered by two firms competing for the exclusive services of workers, who are privately informed about their ability and motivation. Firms differ in their organizational form, and motivated workers are keen to be hired by the non-profit firm because they adhere to its mission. If the for-profit firm has a competitive advantage over the non-profit firm, the latter attracts fewer high-ability workers with respect to the former. Moreover, workers exert more effort at the for-profit than at the non-profit firm despite the latter distorts effort levels upwards. Finally, a wage penalty emerges for non-profit workers which is partly due to compensating effects (labor donations by motivated workers) and partly due to the negative selection of ability into the non-profit firm. The opposite results hold when it is the non-profit firm that has a competitive advantage.
Keywords: D82; D86; J24; J31; M55; 330